Optimal Control Problem To Robust Nonlinear Descriptor control Systems with Matching Condition - Zaboon, Dr. Radhi Ali; Jasim, Sabeeh Lafta (Iraqi Journal of Science, 2022)
Abstract In this paper, the solutions to class of robust non-linear semi-explicit descriptor control systems with matching condition via optimal control strategy are obtained. The optimal control strategy has been introduced and developed in the sense that, the optimal control solution is robust solution to the given non-linear uncertain semi-explicit descriptor control system. The necessary mathematical proofs and remarks as well as discussions are also proposed. The present approach is step-by-step illustrated by application example to show its effectiveness a and efficiency to compensate the structure uncertainty in the given semi-explicit (descriptor) control system